Influence of Internal and External Project Factors On the Performance of Road Construction Project Implementers in West Papua Province - Marjianus Paulus Kioata Tawer; Dewi Ana Rusim; Harmonis Rante (Green Publisher Indonesia, 2024)
The development of road construction projects in West Papua Province is very important to support regional economic development. However, these projects often face challenges that can affect the performance of project implementers. This research aims to identify the influence of internal and external factors on the performance of road construction project implementers in the region. The research method used is a descriptive method with a quantitative approach, where data is collected through questionnaires distributed to project implementers. Data analysis was carried out using regression techniques to determine the relationship between the variables studied. The research results show that internal factors such as project team competency and risk management, as well as external factors such as weather conditions and government regulations, have a significant influence on the performance of project implementers. This research concludes that to improve the performance of road construction projects in West Papua, there needs to be an increase in aspects of internal competence and management as well as adaptation to unexpected external conditions.